2 '-(1H-indol-3-ylmethylene)benzenesulfono-hydrazide - Ali, Hapipah Mohd; Ng, S.W.; Jefrey, B.W.; Yusnita, J. (International Union of Crystallography, 2007)
The molecules of of the title compound, C15H13N3O2S, are linked by N-amino-H center dot center dot O-sulfonyl and N-indolyl-H center dot center dot center dot N-imino hydrogen bonds into a layer.